The Hilliness of U.S. Cities. - Pierce, Joseph; Kolden, Crystal A. (Geographical Review, 2015)
What is a hilly city, and which cities are hilliest? This study outlines a basket of methods for quantifying the differential hilliness of U.S. cities. We rank the 100 largest cities in the contiguous United States, using a selection of eight methods to evaluate their comparative hilliness. We then reflect on how four key 'modes of encounter' with terrain shape human perceptions of urban hilliness: visual, pedestrian, automotive, and imagined/conceptual. Varying priorities among these different modes of encounter shape which of our indices may best correlate with lay understandings of urban hilliness or particular policy problems. We conclude with implications of this work for contemporary geographic scholarship and suggestions for further research, particularly with regard to the political and economic effects of hilliness.